Cultural values and career goal of Gen-X and Gen-Y: a conceptual framework - Ismail, Maimunah (Universal Publishers, 2016)
Purpose: This article proposes a conceptual framework of influence of cultural values oncareer goals of Gen-X and Gen-Y.